1981
DOI: 10.1016/0020-7292(81)90054-0
|View full text |Cite
|
Sign up to set email alerts
|

Hysterectomy in the Hausa/Fulani population in Nigeria

Abstract: Two hundred and sixty-five abdominal hysterectomies performed in Ahmadu Bello University Teaching Hospital, Zaria (ABUTHZ) Nigeria form the basis of this study. The commonest indication for operation was fibroids with or without chronic pelvic inflammatory disease. The low incidence of dysfunctional uterine bleeding and endometriosis and the high incidence of trophoblastic disease were noted. The mortality rate was 0.82%. Compared to other series the morbidity rate was high and this was attributed to advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
3
7
0
Order By: Relevance
“…Sato et al (Sato et al 2000b) in Japan stated that "uterine leiomyomas are the most common pelvic tumors" but provided no data of the actual prevalence among their patients. Others (Ezem and Otubu 1981) have cited a 68% incidence of uterine fibromyomata among their hysterectomy cases in Nigeria. A study from Malaysia (Ravindran and Kumaraguruparan 1998) (Debodinance 2001).…”
Section: Geographic Differencesmentioning
confidence: 99%
“…Sato et al (Sato et al 2000b) in Japan stated that "uterine leiomyomas are the most common pelvic tumors" but provided no data of the actual prevalence among their patients. Others (Ezem and Otubu 1981) have cited a 68% incidence of uterine fibromyomata among their hysterectomy cases in Nigeria. A study from Malaysia (Ravindran and Kumaraguruparan 1998) (Debodinance 2001).…”
Section: Geographic Differencesmentioning
confidence: 99%
“…The peak age for the procedure was the fifth decade (40-49). Estimated age range is 31-60 years (5,8,(10)(11)(12). The average parity in our study was four with a range of 0-11.…”
Section: Discussionmentioning
confidence: 99%
“…This may involve removal of the fallopian tube and ovary depending on clinical indication, age and parity of the woman (4). The procedure is not well embraced in developing countries, in particular Nigeria due to socio cultural reasons (5). Thus, the clinical indication for the procedure should be justifiable.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have documented an increased incidence of uterine leiomyoma in black women and women of African descent. In a study it was found that 9.3% of all gynaecological cases were the uterine leiomyoma 7 . The finding is similar to 9.8% reported from Lokoja Nigeria, but higher than 7.8% and 8.4% reported from two Nigerian cities of Zaria and Ilesa respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally two main operation are availablemyomectomy and hystrectomy. Hystrectomy are usually performed in two to three ways like total abdominal hysterectomy, laporoscopic assisted vaginal hysterectomy and non descendent vaginal hysterectomy(NDVH) 7,8 . In this short period of study attempts are made to highlight clinical presentation and operative treatment provided to the admitted patients.…”
Section: Volume 13 Issue 2 May 2014mentioning
confidence: 99%